Anterior cervical pedicle screw and plate fixation using fluoroscope-assisted pedicle axis view imaging: a preliminary report of a new cervical reconstruction technique - Yukawa, Yasutsugu (Springer-Verlag, 2009)
Anterior procedures in the cervical spine are feasible in cases having anterior aetiologies such as anterior neural compression and/or severe kyphosis. Halo vests or anterior plates are used concurrently for cases with long segmental fixation. Halo vests are bothersome and anterior plate fixation is not adequately durable. We developed a new anterior pedicle screw (APS) and plate fixation procedure that can be used with fluoroscope-assisted pedicle axis view imaging. Six patients (3 men and 3 women; mean age, 54 years) with anterior multisegmental aetiology were included in this study. Their original diagnoses comprised cervical myelopathy and/or radiculopathy (n = 4), posterior longitudinal ligament ossification (n = 1) and post-traumatic kyphosis (n = 1). All patients underwent anterior decompression and strut grafting with APS and plate fixation. Mean operative time was 192 min and average blood loss was 73 ml. Patients were permitted to ambulate the next day with a cervical collar. Local sagittal alignment was characterised by 3.5° of kyphosis preoperatively, which improved to 6.8° of lordosis postoperatively and 5.2° of lordosis at final follow-up. Postoperative improvement and early bony union were observed in all cases. There was no serious complication except for two cases of dysphagia. Postoperative imaging demonstrated screw exposure in one screw, but no pedicle perforation. APS and plate fixation is useful in selected cases of multisegmental anterior reconstruction of cervical spine. However, the adequate familiarity and experience with both cervical pedicle screw fixation and the imaging technique used for visualising the pedicle during surgery are crucial for this procedure.